Pojok Baca Sebagai Upaya Meningkatkan Minat Membaca Siswa di SMPN 6 Moncongloe - Detrin Ombi, Natalia; Arwadi, Fajar; Asmaun, Asmaun; Djam'an, Nurwati; Sidjara, Sahlan; Angraeni, Yuniar; Syukur, Muhammad (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2025)
Student interest reading in Indonesia remains low. Data of UNESCO shows that the Indonesian reading interest index is only 0.001%, it means that only one in 1,000 people enjoy reading. This condition requires a concrete strategy to foster a culture of literacy in schools. One effort that can be done is providing reading corners in classrooms. This article discusses about community service activities at SMPN 6 Moncongloe through the creation of reading corners in grades IX-4. This activity was carried out in three stages: preparation, implementation, and simple evaluation, by actively involving students in the process of arranging and utilizing the reading corners. The results show that the reading corners successfully created a pleasant learning atmosphere, increased reading motivation, and supported the School Literacy Movement (GLS). The obstacles faced were the limited book collection and the need for routine facility maintenance. This activity emphasizes the importance of collaboration between schools, teachers, and parents in building a sustainable literacy culture.